PREPARATION AND ISOMERIZATION OF DICHLOROAMINO-3,5-DIFLUORORO-4- HEPTAFLUOROISOPROPYL-6-METHOXY PYRIDINE (Journal of Sciences, Islamic Republic of Iran)
Treatment of 4-heptafluoroisopropyl-2-methoxy-3,5,6-trifluropyridine (4 ) with aqueous ammonia in THF gave 2-amino-3,5-difluoro-4-heptafluoroisopropyl- 6-methoxy pyridine (5) in 7 1% yield. Chlorination of this amine with 'ButOCl at -16°C gave an unstable product, namely 2-dichloroarnino-3,5- difluoro-4-heptafluoroisopropyl-6-methoxy pyridine (6). Iodine-catalysed rearrangement of this dichloroamino-compound provided a ca. 70:30 mixture of 3-chloro-6-chloroimino-3,5-difluoro- 4-heptafluoroisopropyl-2-methox y -I azacyclohexa- l,4-diene (7) and 5-chloro-6-chloroirnino-3,5-difluoro-4-hepta fluoroisopropyl- 2-methoxy- 1 -azacyclohexa- l,3-diene(8). The C NMR spectra of these imines have also been studied